Relationship of Parenting Styles and the Incident of Overweight Among Pre-School Children Aged 3-5 Years in the Work Area of Puskesmas Kalidoni Palembang - Hardianti; Fatmalina Febry (Faculty of Public Health, Sriwijaya University, 2019)
Obesity has become a global health problem in the world. The impact of obesity is degenerative disease. The style of family care is one of the factors that influence the occurrence of obesity in children. The purpose of this study was to determine the relationship between family care style with obesity in preschool children aged 3-5 years. This study uses a cross sectional design with a total of 143 preschool children aged 3-5 years using Cluster Sampling sampling techniques. research shows that there is a relationship between parental supervision when watching television (pvalue = 0.043) and parental physical activity patterns (pvalue = 0,000), while the most dominant variable is the parental physical activity pattern with a PR value of 15,896. school is influenced by parental supervision when watching television and parental physical activity patterns. It is hoped that all parties can make efforts to prevent obesity in children by increasing physical activity of children such as buying sports equipment and inviting children to exercise and conduct more stringent supervision when children watch television, play games or gadgets.